Determinants of Pakistan’s Relations with Southeast Asian Countries (Journal of Asian Development Studies, 2024)
Pakistan has maintained cordial relations with Southeast Asian countries since its inception, and it introduced a "Vision East Asia" program in 2003 to deepen its political, economic, and cultural links with Southeast Asia. With the exception of Laos, Pakistan now has resident diplomatic representations in all Southeast Asian countries. Pakistan's "Look East Policy" primarily aims to boost trade and lure investors. However, there has not been a discernible growth in commerce between Pakistan and these nations, and the potential has not yet been fully realized. Pakistan is attempting to sign bilateral FTAs with these nations through multilateral agreements. Further, Pakistan can enhance its maritime cooperation with these states. Moreover, Pakistan can strengthen its bilateral ties with China, connecting the region through its One Belt One Road initiative.